The Left and universal basic income: the role of ideology in individual support - Schwander, H; Vlandas, T (Cambridge University Press, 2020)
Few studies to date have analysed individual support for universal basic income (UBI). This article theorizes and explores empirically the relationship between different strands of left ideology and support for UBI across European countries. We delineate three types of concerns about capitalism: “Labourist Left” worry about exploitation; “Libertarian Left” about repression and “Social Investment Left” about inefficiencies. Contrary to expectations we derive from political theory and welfare state literature, our results based on data from the European Social Survey suggest that having high concerns about exploitation is positively correlated with support for UBI, whereas repression concerns are negatively correlated with support. In line with our hypothesis about social investment ideology, left-leaning individuals with efficiency concerns are more likely to support UBI. Our findings call for more detailed surveys as well as further research on the different ideologies within the Left and how these relate to variation in support for UBI, which crucially shapes the potential political coalition behind the introduction of UBI.